PERANCANGAN INTERIOR HOTEL RESORT ALILA VILLAS DENGAN TEMA ENVIRONMENTALLY GREEN DESIGN DI ULUWATU, BALI - Suwanto, Garnike Feronia; Hermono, Emilius Heri (Anggada : Jurnal Desain dan Seni, 2021)
The concept of Green Design is a regional development concept for environmentally friendly tourism activities. Green Design is a form of implementation of the concept of sustainable design (sustainable development), which is the first step for the community to participate in protecting the environment. In addition to the decline in the tourism and economic sectors, the national tourism sector is also faced with climate change so that the tourism industry sector is capable in all aspects, one of which is environmental conservation in the context of sustainable economic development. One of the buildings that needs to pay attention and plan a green design on the interior of its resort hotel is Hotel Resort Alila Villas Uluwatu by applying ventilation and materials used to support green design in each room and implementing the Covid-19 health protocol in the current pandemic era. The purpose of this study is to help the environment with sustainable development-oriented designs in order to create an interior hotel resort that can have a positive impact on the environment and its residents. The design method used is descriptive qualitative method, starting with collecting data, analyzing data, developing the design and the final stage of the design. The design that will be applied is with the theme "Environmentally Green Design with Tropical Modernism" with the aim of creating a Resort Hotel interior that has a good impact on the environment and its users. The expected results in this design can provide an eco-friendly resort hotel interior through the application of Green Design aspects on interior elements and together reduce the negative impact of global warming and optimize optimal room ventilation in the current Covid-19 pandemic.